2019
DOI: 10.1142/s2010135x19500073
|View full text |Cite
|
Sign up to set email alerts
|

The electronic structure and optical properties of Ca3(Mn1−xTix)2O7from first-principle calculations

Abstract: The electronic structure and optical properties of Ca3(Mn[Formula: see text]Ti[Formula: see text]O7 ([Formula: see text], 1/8, 2/8, 3/8, 4/8) were studied by first-principle calculations within the generalized gradient approximation approaches (GGA). The lattice constants of Ca3(Mn[Formula: see text]Ti[Formula: see text]O7 increase with the increase of Ti[Formula: see text] content caused by the substitution of Ti[Formula: see text] with larger ionic radius for Mn[Formula: see text]. Ca3(Mn[Formula: see text]T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This is indicated by the DOS diagrams calculated for the following model compounds: undoped (Ca 12 Mn 8 O 28 ), La‐doped (Ca 11 LaMn 8 O 28 ), and Y‐doped (Ca 11 YMn 8 O 28 ) shown in Figure 11a,b. The band gap was calculated to be 0.936 eV, which is twice as higher as the DFT computed band gap of 0.384 eV, 56 and closer to the experimental value of 1.29 eV 57 . As shown in the DOS of the undoped Ca 3 Mn 2 O 7 , the conduction band minimum (CBM) consists of Mn‐3d states mainly, explaining the immediate effect of Hubbard U‐correction on the band gap, whereas the valence band maximum (VBM) consists of O‐2p states mostly, with minor contribution only from Mn‐3d states.…”
Section: Resultsmentioning
confidence: 70%
“…This is indicated by the DOS diagrams calculated for the following model compounds: undoped (Ca 12 Mn 8 O 28 ), La‐doped (Ca 11 LaMn 8 O 28 ), and Y‐doped (Ca 11 YMn 8 O 28 ) shown in Figure 11a,b. The band gap was calculated to be 0.936 eV, which is twice as higher as the DFT computed band gap of 0.384 eV, 56 and closer to the experimental value of 1.29 eV 57 . As shown in the DOS of the undoped Ca 3 Mn 2 O 7 , the conduction band minimum (CBM) consists of Mn‐3d states mainly, explaining the immediate effect of Hubbard U‐correction on the band gap, whereas the valence band maximum (VBM) consists of O‐2p states mostly, with minor contribution only from Mn‐3d states.…”
Section: Resultsmentioning
confidence: 70%
“…For Fe substituted in Ca 3 Ti 2 O 7 ceramics, its optical band gap decreases from 3.61 to 2.23 eV, which is attributed to the Fe substitution induces disorder and broadens the gap edge of absorption [92]. Meanwhile, the direct band gap with the semiconductor behaviour of Ca 3 (Mn 1−x Ti x ) 2 O 7 was proved using DFT calculations, which indicated that the bandgap increases with the increase in Ti 4+ content, and the introduction of nonmagnetic Ti 4+ ions weakens the magnetism [93]. A small amount of Li substitution in Ca 3 Mn 2 O 7 remarkably decreases oxygen vacancies, which introduces disorder and results in the widening of the band gap [94].…”
Section: Compoundsmentioning
confidence: 97%
“…Moreover, the antiferromagnetic (AFM) Neel temperature of La‐doped Ca 3 Mn 2 O 7 was enhanced from 100 to 130 K, 13 and weak ferromagnetism has been introduced successfully in the G‐type AFM (G‐AFM) Ca 3 Mn 2 O 7 by Li doping 14 . In addition, more works analyzed the electronic configuration, optical, dielectric, and other properties of Ca 3 Mn 2 O 7 by the first‐principles calculations 15–17 . However, previous studies were mainly focused on the A‐site doping to realize the transformation from antiferromagnetism to ferromagnetism in Ca 3 Mn 2 O 7 , but the B‐site doping was rarely studied.…”
Section: Introductionmentioning
confidence: 99%
“…14 In addition, more works analyzed the electronic configuration, optical, dielectric, and other properties of Ca 3 Mn 2 O 7 by the first-principles calculations. [15][16][17] However, previous studies were mainly focused on the A-site doping to realize the transformation from antiferromagnetism to ferromagnetism in Ca 3 Mn 2 O 7 , but the B-site doping was rarely studied.…”
Section: Introductionmentioning
confidence: 99%